Analysis of the Legal Effects of Default in the Sale and Purchase Agreement for Agricultural Facilities against the Parties (Case Study of District Court Decision Source Number 30/Pdt.G/2022/PN Sbr) - Rahmah Nurazizah, Maulina; Shabrinah, Luthfiyah; Mayana, Sinta; Rahman, Alip; Dikrurahman, Diky (Pelopor Publikasi Akademika, 2024)
The legal basis for assessing a default case is Article 1238 of the Civil Code which explains that a default occurs when the debtor does not fulfill its obligations according to the agreement. A tort lawsuit is a civil lawsuit that refers to default in an agreement and is submitted through a lawsuit letter, where letter evidence has an important role in proving the claim. In the decision of this case, the court considers the evidence and suitability between the claim and the relevant legal basis for making a decision in the case. Factors such as the location of the collateral object, differences in the name of the landowner, and the clarity of the goods auctioned are the main considerations in determining the granting of the lawsuit and the rejection of the application for auction of collateral. The results showed that the Source District Court used Article 1238 of the Civil Code as a legal basis in assessing cases of default in the sale and purchase agreement of agricultural facilities, with a letter of agreement as the main evidence. The factors that caused some of the Plaintiff's claims to be granted and some of the Defendants' requests for auction of debt collateral were the discrepancy between the description of the lawsuit and the evidence of the letter submitted, especially regarding the location of the collateral object, differences in the name of the landowner, and the vagueness of the goods to be auctioned.